J. W. Simonton petition - Simonton, J. W. (John Watson), approximately 1789-1854.
Printed petition, signed by Simonton and addressed to members of Congress, requesting the establishment of a court in Key West, Fla.
Businessman, of Key West, Fla.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Courts -- Florida -- Key West; Businessmen